A Study of Solo-Livers in Eastern Asia: an Eye on Japan, China and South Korea - Muradyan, Olena; Yashkina, Daria; Мурадян, Олена; Яшкіна, Дар’я (Волинський національний університет імені Лесі Українки, 2020)
The article examines how the processes of individualization (which in the modern world lead to many social changes, including lifestyle changes) alter the attitude to the need to start a family. Such processes also lead to the emergence of such phenomenon as "solo-living", but the analysis of the existing studies has shown that the growth of singles has not been researched in global comparative studies. The authors analyze how the problem of singles' growth in East Asian countries (with the focus on Japan, China and South Korea) is considered. Asian studies show that the lifestyle of single people is dictated by several reasons: lack of free time due to work (imbalance between work and life outside it), opposition of young people to official policies of their countries (social policy is aimed at supporting family traditions) and support for such lifestyle by marketing companies (the market is increasingly focused on singles in these countries). Prospects for further research include considering confrontation of social policies of the states and market policy on the issue of solo-living and the analysis of local studies of solo-living. Процеси індивідуалізації в сучасному світі призводять до багатьох соціальних змін, у тому числі й до змін стилів життя. Змінюється ставлення до необхідності створення сім’ї, починають виникати такі феномени, як «solo-living», проте зростання одинаків не досліджується в рамках глобальних порівняльних досліджень. У межах статті проводиться аналіз того, яким чином розглянуто проблему зростання одинаків у країнах Східної Азії на прикладах Японії, Китаю та Південної Кореї. Автори роблять висновок, що азіатські дослідження демонструють тенденцію, що стиль життя одинаків продиктований нестатком вільного часу через трудову діяльність, протистоянням молоді офіційним політикам своїх держав та підтримкою такого стилю життя маркетинговими компаніями. Перспективами подальшого дослідження тематики є розгляд протистояння соціальних політик держав і політики ринку щодо питання solo-living. Процессы индивидуализации в современном мире приводят ко многим социальным изменениям, в том числе и к изменениям стилей жизни. Меняется отношение к необходимости создания семьи, начинают возникать такие феномены, как «solo-living», при этом рост одиночек не исследуется в рамках глобальных сравнительных исследований. В рамках статьи проводится анализ того, каким образом рассматривается проблема роста числа одиночек в странах Восточной Азии на примерах Японии, Китая и Южной Кореи. Авторы приходят к выводу: азиатские исследования показывают, что стиль жизни одиночек продиктован недостатком свободного времени из-за трудовой деятельности, противостоянием молодежи официальным политикам своих государств и поддержкой такого стиля жизни маркетинговыми компаниями. Перспективами дальнейшего исследования тематики является рассмотрение противостояния социальных политик государств и политики рынка по вопросу solo-living.
Дослідження життя соло в Східній Азії: погляд на Японію, Китай та Південну Корею
Keywords: social change; lifestyle; solo-living; public and private space; South Asia; соціальні зміни; стиль життя; публічний і приватний простір; Східна Азія; социальные изменения; стиль жизни; публичное и приватное пространство; Восточная Азия; 316.42:316.728